An Analysis of Indian Firm Levels’ Digital Finance, ESG Performance, and Financial Performance: A Road Map to Long-Term Sustainability (Don Bosco Institute of Technology Delhi Journal of Research, 2025)
This research aims to investigate the processes for using digital finance to  address the sustainability triple-bottom-line challenge, as digital finance is  essential for attaining sustainability. Within the context of digital finance,  this article investigates the inner workings of the relationship between  financial performance and ESG (environmental, social, and governance)  factors. Indirectly improving both short- and long-term financial success  for organizations, digital finance promotes ESG performance, according  to the research. Furthermore, the key enabler for ESG and short-term  financial success is the depth of digital finance adoption. According to the  results of the mechanism study, improving green innovation and bolstering  digital transformation would strengthen the favorable correlation between  digital finance and ESG. Furthermore, according to heterogeneity study,  big businesses and SOEs (state-owned enterprises) have a stronger positive  effect on ESG and financial performance when it comes to digital finance  use depth, but small firms and non-SOEs have a stronger positive effect on  ESG when it comes to coverage breadth. By outlining potential avenues for  sustainable behavior, this article deepens our understanding of digital money.
Keywords: Digital Finance; India; Sustainability; ESG; Financial Performance; Digital Finance.